2008
DOI: 10.1080/01140670809510244
|View full text |Cite
|
Sign up to set email alerts
|

Modelling flower production of kiwifruit (Actinidia deliciosa) from winter chilling

Abstract: In warm areas of New Zealand the productivity of kiwifruit vines (Actinidia deliciosa) can be limited by the low number of flowers produced following a warm winter. Our objective was to formulate a model that quantifies how temperatures, use of hydrogen cyanamide (HC), and orchard location affect flower production of kiwifruit vines. Flowering of kiwifruit vines, and winter temperatures, were monitored in a range of climates in New Zealand for 6 years. Mean winter temperatures for the period May-July ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Plant dormancy has been divided into three well-defined phases, para-, endo-, and eco-dormancy ( Lang et al , 1987 ). While growth can resume during para- and eco-dormancy, accumulation of chilling is required to release endo-dormancy, to allow budbreak and floral competency in the following spring ( Linsley-Noakes and Allan, 1987 ; Walton et al , 2001 ; Snelgar et al , 2008 ). The normal chilling requirement for A. deliciosa ‘Hayward’ is ~800 h ( Linsley-Noakes and Allan, 1987 ), after which dormancy is fully alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…Plant dormancy has been divided into three well-defined phases, para-, endo-, and eco-dormancy ( Lang et al , 1987 ). While growth can resume during para- and eco-dormancy, accumulation of chilling is required to release endo-dormancy, to allow budbreak and floral competency in the following spring ( Linsley-Noakes and Allan, 1987 ; Walton et al , 2001 ; Snelgar et al , 2008 ). The normal chilling requirement for A. deliciosa ‘Hayward’ is ~800 h ( Linsley-Noakes and Allan, 1987 ), after which dormancy is fully alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent research has shown that the development of models for the number of kiwi flowers, should consider the "long-term" temperature of the site by introducing corrective coefficients (Snelgar et al 2008). Tryjanowski et al (2006) hypothesized that the diverse patterns of phenological behavior in the horse chestnut and violet in Great Britain and Poland could be ascribed to local species adaptation.…”
Section: Phenological Modellingmentioning
confidence: 99%